Catastrophic landslides, glacier behaviour and moraine formation – A view from an active plate margin - Shulmeister, J.; Davies, T.R.; Evans, D.J.A.; Hyatt, O.M.; Tovar, D.S. (Quaternary Science Reviews, 2009)
The influence of large bedrock landslides (‘‘rock avalanches’’) on the behaviour of glaciers is incompletely recognised. Here we present an example from an active tectonic margin in South Island, New Zealand where large earthquakes leave a significant imprint on glacial records. We demonstrate that terminal moraines on the western side of the Southern Alps record both ‘ordinary’ (i.e. climate-driven) and landslide-initiated glacial advances. Following consideration of the processes involved in rock avalanche initiated moraine construction we suggest ways of determining the nature of the advance that built the terminal moraine. The implications of these observations are important in breaking the conventional linkage of individual terminal moraines with climate forcing.
EPrint Processing Status: Author unable to supply full text